(untitled) (Modern Problems of Metallurgy, 2025)
The object of the study is the metallurgical technology of chipboard dust processing and iron-containing waste from metallurgical production. The purpose of the work is the analysis of physical and chemical processes, experimental research and the development of innovative technological solutions and recommendations for chipboard dust and iron-containing metallurgical waste. Research methods – theoretical research is based on the basic principles of physical chemistry and the theory of metallurgical processes. Calculations of the thermodynamic equilibrium of oxide systems are based on the Gibbs theory and implemented using the computer program "FASTSage 6.0"; the chemical composition of the phase components of manganese ferroalloys was studied using a scanning electron microscope YSM-6300LA from JEOL, Japan. Scientific novelty. Effective removal of zinc from chipboard dust is already possible at moderate temperatures of 1000...1100oC, including when using substandard carbon materials as a carbon reducer. To obtain a liquid product, it is necessary to provide an excess amount of carburizing carbon to lower the temperature of the resulting melt. At temperatures of the order of 1000...1100°С, iron-containing dust and sludge undergo changes, which leads to a decrease in the content of Zn in the processed material, the transition of the original dust-like materials into a compact mass. Practical meaning. The joint processing of chipboard slag and dust by dosing in different proportions is not rational, because in this case the concentration of zinc collected in the gas cleaning processing unit is reduced. It will be more effective to organize alternate processing of chipboard dust and slag at different time periods (for example, monthly).